Prophylactic corticosteroid use in patients receiving axicabtagene ciloleucel for large B‐cell lymphoma. (22nd July 2021) - Oluwole, Olalekan O.; Bouabdallah, Krimo; Muñoz, Javier; De Guibert, Sophie; Vose, Julie M.; Bartlett, Nancy L.; Lin, Yi; Deol, Abhinav; McSweeney, Peter A.; Goy, Andre H.; Kersten, Marie José; Jacobson, Caron A.; et al.
Summary: ZUMA‐1 (NCT02348216) examined the safety and efficacy of axicabtagene ciloleucel (axi‐cel), an autologous CD19‐directed chimaeric antigen receptor (CAR)‐T cell therapy, in refractory large B‐cell lymphoma. To reduce treatment‐related toxicity, several exploratory safety management cohorts were added to ZUMA‐1. Specifically, cohort 6 investigated management of cytokine release syndrome (CRS) and neurologic events (NEs) with prophylactic corticosteroids and earlier corticosteroid and tocilizumab intervention. CRS and NE incidence and severity were primary end‐points. Following leukapheresis, patients could receive optional bridging therapy per investigator discretion. All patients received conditioning chemotherapy (days −5 through −3), 2 × 10 6  CAR‐T cells/kg (day 0) and once‐daily oral dexamethasone [10 mg, day 0 (before axi‐cel) through day 2]. Forty patients received axi‐cel. CRS occurred in 80% of patients (all grade ≤2). Any grade and grade 3 or higher NEs occurred in 58% and 13% of patients respectively. Sixty‐eight per cent of patients did not experience CRS or NEs within 72 h of axi‐cel. With a median follow‐up of 8·9 months, objective and complete response rates were 95% and 80% respectively. Overall, prophylactic corticosteroids and earlier corticosteroid and/or tocilizumab intervention resulted in no grade 3 or higher CRS, a low rate of grade 3 or higher NEs and high response rates in this study population.